Number Theory and Its Applications - Seoung Ryoo, Cheon; Seoung Ryoo, Cheon (IntechOpen, 2020)
Number theory and its applications are well known for their proven properties and excellent applicability in interdisciplinary fields of science. Until now, research on number theory and its applications has been done in mathematics, applied mathematics, and the sciences. In particular, number theory plays a fundamental and important role in mathematics and applied mathematics. This book is based on recent results in all areas related to number theory and its applications.
English
Keywords: Discrete mathematics; Discrete mathematics